Association between response rates and survival outcomes in patients with newly diagnosed multiple myeloma. A systematic review and meta‐regression analysis. (20th March 2017) - Mainou, Maria; Madenidou, Anastasia‐Vasiliki; Liakos, Aris; Paschos, Paschalis; Karagiannis, Thomas; Bekiari, Eleni; Vlachaki, Efthymia; Wang, Zhen; Murad, Mohammad Hassan; Kumar, Shaji; Tsapas, Apostolos
Abstract: Objectives: We performed a systematic review and meta‐regression analysis of randomized control trials to investigate the association between response to initial treatment and survival outcomes in patients with newly diagnosed multiple myeloma (MM). Methods: Response outcomes included complete response (CR) and the combined outcome of CR or very good partial response (VGPR), while survival outcomes were overall survival (OS) and progression‐free survival (PFS). We used random‐effect meta‐regression models and conducted sensitivity analyses based on definition of CR and study quality. Results: Seventy‐two trials were included in the systematic review, 63 of which contributed data in meta‐regression analyses. There was no association between OS and CR in patients without autologous stem cell transplant (ASCT) (regression coefficient: .02, 95% confidence interval [CI] −0.06, 0.10), in patients undergoing ASCT (−.11, 95% CI −0.44, 0.22) and in trials comparing ASCT with non‐ASCT patients (.04, 95% CI −0.29, 0.38). Similarly, OS did not correlate with the combined metric of CR or VGPR, and no association was evident between response outcomes and PFS. Sensitivity analyses yielded similar results. Conclusions: This meta‐regression analysis suggests that there is no association between conventional response outcomes and survival in patients with newly diagnosed MM.